Investigating the common themes of the story "Pir Rabab Nawaz in Attar's tragedy" with "Pir Changi in Rumi's spiritual Masnavi" from the perspective of form and meaning - Mohamad dost, Reza; Ashrafzadeh, Reza; mahdavidamghani, Mahmud (International Journal of Psychosocial Rehabilitation, 2021)
Finding common themes and concepts in similar stories, both in form and content, set in the same era or over a longer period of time leads us to the conclusion that many poets and writers are influenced by a particular school. Or a person has become an indicator and has brought his various ideas closer to it in form and meaning and has produced different results. Since Rumi has been influenced by Attar's thoughts in composing and creating his poetic stories in the book MasnaviManavi and has followed them in many cases, by comparing and examining the stories and anecdotes in the works of two precious poets, concepts and themes can be found. Common found that the high frequencies in the works of both indicate the importance of their mystical ideas. In a study of about thirty-four (story or anecdote or story) between the works of two great poets have some commonalities, some have common characters of time, place and the rest of the components of storytelling, however, some in different final results. . .اندRegardless of the components of today's storytelling, the observance of which adds to the quality of the story, in this quest and the allusions that will be made, only the general aspect of it will be considered and other cracks (story, anecdote) will also be called stories. Although Attar was a pioneer in the field of storytelling over Rumi, but in general, the observance of some components of storytelling based on modern patterns can be found and matched in both poets.